LEGAL DISCOVERY BY JUDGES IN ADDRESSING THE AMBIGUITY OF “DEALER” AND “USER” ELEMENTS IN ARTICLES 114, 112, AND 127 OF THE NARCOTICS LAW - Irwan Triadi; Dhikma Heradika; Abelmart Sihombing; Bayu Giri Atmojo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The ambiguity of the elements “dealer” and “user” in Articles 114, 112, and 127 of Law Number 35 of 2009 on Narcotics creates legal uncertainty in the practice of criminal justice. These three provisions often overlap in law enforcement, particularly when investigators and public prosecutors apply more severe charges without comprehensively examining the legal construction of the defendant’s actions, including the social and situational context behind them. This study is a normative legal research that examines the doctrine of judicial legal discovery, principles of criminal law, and the principle of proportionality in sentencing in a more in-depth and structured manner. The results of the study indicate that judges have the authority to interpret the elements of narcotics criminal acts systematically, grammatically, and teleologically to clearly distinguish between “abusive users” and “dealers with the intent to distribute.” Legal discovery is needed to prevent overcriminalization and to ensure the protection of the rights of suspects and defendants throughout the entire criminal justice process. This study concludes that the appropriate method of interpretation is an integration of systematic interpretation, teleological interpretation, and the ratio legis of the Narcotics Law.